2015
DOI: 10.1097/jim.0000000000000239
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin Measurement in the Critically Ill

Abstract: BackgroundElevated cardiac troponin (cTn) in the absence of acute coronary syndromes (ACS) is associated with increased mortality in critically ill patients. There are no evidence-based interventions that reduce mortality in this group.ObjectivesWe performed a retrospective investigation of the Veterans Administration Inpatient Evaluation Center database to determine whether drugs used in ACS (β-blockers, aspirin, and statins) are associated with reduced mortality in critically ill patients.MethodsThirty-day m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Additionally, data on medications that may be cardioprotective were also not available. This latter effect was recently studied by Poe et al who found that statins, β-blockers and aspirin have the potential to modify the mortality in patients with elevated cardiac troponin-I [ 27 ]. Notably, they showed that patients with no or intermediate elevation in cardiac troponin-I taking statins within 24 h of measurement had a lower mortality than those not taking statins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, data on medications that may be cardioprotective were also not available. This latter effect was recently studied by Poe et al who found that statins, β-blockers and aspirin have the potential to modify the mortality in patients with elevated cardiac troponin-I [ 27 ]. Notably, they showed that patients with no or intermediate elevation in cardiac troponin-I taking statins within 24 h of measurement had a lower mortality than those not taking statins.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike patients with STEMI, who myocardial infarction due to an atherosclerotic plaque, [ 28 ] troponin-I elevation in general ICU patients is seldom related to obstructive coronary disease [ 1 ]. They usually experience Type II MI secondary to a variety of factors that increase mismatch between myocardial oxygen supply and demand; these include tachycardia, shock, vasopressors, inotropes, hypoxemia, anemia, and hypertension [ 27 ]. The mechanism of myocardium injury is important because most of data on MI treatment come from studies on Type I MI, and there are little data regarding the treatment of Type II MI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac troponins are consistently associated with worse outcomes in critical illness, [33][34][35][36][37] and cardiac biomarkers may be modifiable by administration of albumin 34 and medications. 35 Given that coronary blood flow is maintained over a broad range of coronary perfusion pressures under most circumstances, 38 we hypothesise that increasing vasopressors to achieve a higher MAP will have little effect on coronary perfusion but may increase the severity of demandrelated myocardial ischaemia via increased heart rate (ie, reduced coronary perfusion time) and transmural pressure (ie, afterload). If OVATION-65 shows that permissive hypotension prevents or limits hsTnT elevation, then patients at increased risk of secondary myocardial ischaemia, possibly identified by baseline hsTnT, may benefit the most from this strategy.…”
Section: Primary Outcomementioning
confidence: 99%
“…Myocardial injury is common in critically ill people 1 , 2 and dogs. 3 , 4 , 5 Confirmation of cellular injury requires biomarkers reflective of content leakage from the cell.…”
Section: Introductionmentioning
confidence: 99%